The Implementation of an Online Distance Learning Program with an Independent Curriculum-Based on Improving Child-Parent Relations - Lutviatiani, Mita; Shofiyah , Nenny Chanidatus; Wijaksono , Cahyo Febri; Zawawi , Ahmad Abdullah (Educative: Jurnal Ilmiah Pendidikan, 2023)
The transition from the 2013 curriculum (K-13) to the Independent Curriculum in Indonesia represents an evaluative measure aimed at enhancing the overall educational standards in the country. Homeschooling Kak Seto Surabaya is a non-formal educational institution program that incorporates an independent curriculum. The establishment of a strong and effective partnership between students and parents plays a pivotal role in the attainment of learning objectives within distance learning programs. Hence, the purpose of this study was to examine the implementation of the independent learning curriculum in the context of distance learning programs, specifically focusing on its impact on enhancing the parent-child relationship within the Homeschooling Kak Seto Surabaya. The employed methodology is a qualitative approach utilizing a case study design. The employed methodology for data collection encompassed participatory observation as well as semi-structured interviews conducted with both managers and parents of students. The data analysis model utilized in this study is the Miles and Huberman model, which encompasses the sequential stages of data collection, data reduction, data presentation, and drawing conclusions. The findings of this study indicate that the implementation of an independent curriculum has a significant impact on enhancing the relationship between children and parents during the learning process.